Problematyka wychowania społecznego w posoborowym nauczaniu Kościoła - Stanisław Dziekoński (Studia Ecologiae et Bioethicae)
The issue of social education has an important place in the teaching of the Church. In the pronouncements of the II Vatican Council the need for the formation of the basis of the constructive and responsible participation of children in social life has been noted. Such directions of education have been developed in the teaching after the Council. Even more strongly has it been underlined that the integral education of man demands formation towards the essential values of human life and a gradual introduction of children to responsibility for the formation of the civilization of love in the contemporary world. A large part of the pronouncements of the Church and of the Popes must be seen as the reaction to the changes taking place in the world. But, independently from the period of history, the Church has always underlined the irreplaceable and primary role of the family in the personal-social education of the child.